2020
DOI: 10.3390/polym12030561
|View full text |Cite
|
Sign up to set email alerts
|

Plasticization of Polylactide after Solidification: An Effectiveness and Utilization for Correct Interpretation of Thermal Properties

Abstract: Polylactide/triethyl citrate (PLA/TEC) systems were prepared in two ways by introducing TEC to solidified polymer matrix (SS) and by blending in a molten state (MS) to investigate the effectiveness of the plasticization process after solidification of polylactide. The plasticization processes, independent of the way of introducing the TEC into PLA matrix, leads to systems characterized by similar stability, morphology, and properties. Some differences in mechanical properties between MS and SS systems result p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…This discrepancy is likely related to several factors, including the difference in the thermal conductivity of the filler and polymer matrix, the nucleation efficiency (NE) of the filler, its state of dispersion within the matrix, and the potential existence of mechanisms of interfacial crystallization such as epitaxy and transcrystallization [ 29 , 30 , 31 , 32 ]. NE is strongly dependent on the nanofiller morphology, its surface energy, roughness, and crystalline structure as well as on the filler ability to form the critical nucleus [ 16 , 17 , 33 , 34 ]. Furthermore, the dependence of crystallinity (1-λ) c of PLLA and its 2D-WS 2 nanocomposites as a function of cooling rate ( Figure 5 a) closely mirrors the T p trends previously mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy is likely related to several factors, including the difference in the thermal conductivity of the filler and polymer matrix, the nucleation efficiency (NE) of the filler, its state of dispersion within the matrix, and the potential existence of mechanisms of interfacial crystallization such as epitaxy and transcrystallization [ 29 , 30 , 31 , 32 ]. NE is strongly dependent on the nanofiller morphology, its surface energy, roughness, and crystalline structure as well as on the filler ability to form the critical nucleus [ 16 , 17 , 33 , 34 ]. Furthermore, the dependence of crystallinity (1-λ) c of PLLA and its 2D-WS 2 nanocomposites as a function of cooling rate ( Figure 5 a) closely mirrors the T p trends previously mentioned.…”
Section: Resultsmentioning
confidence: 99%
“…The long period of PLA/modifier systems was determined by two-dimensional (2D) small-angle X-ray scattering (SAXS) utilizing the equipment and methods described elsewhere. , …”
Section: Methodsmentioning
confidence: 99%
“…It exhibits a wide application potential in the field of packaging materials because of its high degradability, extraordinary transparency, good mechanical strength, and easy processability. However, PLA has several limitations (brittleness, stiffness, poor ability to plastic deformation, and poor gas barrier properties) and requires significant property improvement to fulfill the specific functional requirements in such applications. In a previous work, we showed that as a result of introducing triethyl citrate (TEC) into the PLA matrix and its accumulation into the interlamellar/interspherulitic regions, a system with enhanced flexibility and toughness is obtained. In this work, we verified how the modification with the use of various low molecular weight compounds (TEC; glycerol, Gly; and polyethylene glycol, PEG) with clearly different Hildebrand solubility parameters affects the molecular packing efficiency of the amorphous phase of PLA (increase or decrease in the pore size of the free volume) and determine the final transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy is likely related to several factors and none can be ruled out: the difference in the thermal conductivity of the filler and polymer matrix; the nucleation efficiency (NE) of the filler; its state of dispersion within the matrix; and the potential existence of mechanisms of interfacial crystallization such as epitaxy and transcrystallization [ 6 , 7 , 8 , 9 ]. In addition, NE is strongly dependent on the nanofiller morphology, its surface energy, roughness and crystalline structure as well as on the filler’s ability to form the critical nucleus [ 10 , 11 ]. In this regard, Jabbarzadeh has recently reported the crystallization origin in nanocomposite polymers [ 12 ].…”
Section: Introductionmentioning
confidence: 99%